The Effect of Income Expectations, Entrepreneurial Knowledge, and Entrepreneurial Mindset on Interest in Entrepreneurship, with Self-Efficacy as A Mediating Variable, Among KPK Civil Servants in the 2025 Cohort - M Syaifudin Kafi; Saparuddin Mukhtar; Agung Dharmawan Buchdadi (Return : Study of Management, Economic and Bussines, 2026)
Civil servants have increasingly gained opportunities to engage in entrepreneurial activities; however, the actual level of entrepreneurial participation remains relatively low. This condition indicates that regulatory opportunities alone are insufficient to encourage entrepreneurial interest, as psychological and cognitive factors may play important roles in shaping entrepreneurial intentions. This study aims to examine the effects of income expectations, entrepreneurial knowledge, and entrepreneurial mindset on entrepreneurial interest while analyzing the mediating role of entrepreneurial self-efficacy among KPK civil servants in the 2025 cohort. This study employed a quantitative approach using a survey method involving 133 respondents. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results showed that income expectations, entrepreneurial knowledge, and entrepreneurial mindset significantly and positively affected self-efficacy. Furthermore, self-efficacy had a significant positive effect on entrepreneurial interest. Income expectations and entrepreneurial knowledge also directly influenced entrepreneurial interest, whereas entrepreneurial mindset did not have a direct significant effect. However, self-efficacy fully mediated the relationship between entrepreneurial mindset and entrepreneurial interest, demonstrating that mindset influences entrepreneurial intention through increased confidence in entrepreneurial capabilities. The study concludes that strengthening self-efficacy, particularly through entrepreneurial mindset development, is essential to encourage entrepreneurial interest among civil servants within a high-integrity institutional environment.